PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK ELEKTRONIK DILENGKAPI TUGAS PROYEK MATERI PERUBAHAN LINGKUNGAN UNTUK FASE E SMA/MA - Kasmila Yuhera; Annika Maizeli; Liza Yulia Sari (EDUBIOLOCK, 2024)
In learning activities, teaching materials play a very important role. Open materials include printed books, modules, student worksheets, and handouts. Open materials in the form of printed books in schools are considered inadequate amidst the spread of technology that is currently developing and the student worksheets used does not meet the components of the worksheet elements. Based on this, a study has been conducted that aims to produce an Electronic student worksheets equipped with project assignments on changes in environmental material that are valid and practical. This study uses a research and development method often called research and development (R&D). This research instrument uses two questionnaires, namely the validity of the questionnaire and the practicality of the questionnaire using a Likert scale. The validity test was carried out by filling out the questionnaire by three lecturers while the practicality test was carried out by one biology teacher and 36 students at State Senior High School 16 Padang. The data obtained were analyzed using percentages and processed with descriptive analysis. The results of data analysis on the validity test of the Electronic Student Worksheet equipped with project assignments by the validator show that the Electronic Student Worksheet equipped with project assignments is in the very valid criteria with an average value of 92% and the practicality value of the Electronic Student Worksheet equipped with project assignments by the teacher is very practical criteria with an average value of 97% and by students, the criteria are very practical with an average of 94.4%. It can be concluded that the Electronic Student Worksheet equipped with project assignments on the material of environmental change for Phase E of Senior High Schools that was developed is very valid and practical.